Evaluation of the recovery of areas invaded by silver wattle in the Paisagem Protegida da Serra do Açor - Santos, Catarina Sofia Vicente dos (2021)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia